2008
DOI: 10.1055/s-0039-1697364
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Dental Erosion: A Case Report

Abstract: Chemical erosion is the loss of superficial tooth structure by chemical action in the continued presence of demineralizing agents. This can be prominent in patients with oral habits such as constant citrus ingestion (like lemon chewing), chlorinated swimming pool water or gastrointestinal problems that produce repeated exposure of teeth to gastric acids. In this case report, a multidisciplinary approach to restore the severe wear due to dental erosion by proper techniques and materials was presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The patient had a clinical history of an excessive, prolonged intake of medications and a carbonated and acidic diet. It has been reported that the use of medications causes xerostomia, therefore decreasing the capacity of the saliva buffer (14). The multiple NCCL caused excessive demineralization of the dental structure, thus the loss of vertical dimension.…”
Section: A B C Discussionmentioning
confidence: 99%
“…The patient had a clinical history of an excessive, prolonged intake of medications and a carbonated and acidic diet. It has been reported that the use of medications causes xerostomia, therefore decreasing the capacity of the saliva buffer (14). The multiple NCCL caused excessive demineralization of the dental structure, thus the loss of vertical dimension.…”
Section: A B C Discussionmentioning
confidence: 99%
“…Patients with constant eating habits such as the ingestion of citrus fruits, contact with chlorinated pool water or gastrointestinal problems that produce a repeated exposure of the teeth to hydrochloric acid present in gastric juice may develop acid erosion. Considering that the pH of citric acid is 2.5 and the critical point at which enamel dissolves is the pH range of 5.0-5.7, citric acid may play a significant role in tooth erosion [ 13 ]. It is therefore relevant to diagnose acid erosion at the anamnesis and clinical examination to institute better treatment before the aesthetic rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…A bite plaque is essential for protecting the teeth from erosion and maintaining the vertical dimension of occlusion through the mutually protected occlusion [ 13 ]. The occlusal bite guard is made after the completion of the treatment and is designed for continuous use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva, with its buffering capacity and its ability to form a protective enamel pellicle, can control dental decalcification (23). The reduction in loss of salivary buffering capacity would contribute to the process of enamel erosion (24). Assessing salivary parameters such as pH and buffering capacity in the dental office is possible using commercially available diagnostic kits.…”
mentioning
confidence: 99%